Endotoxin-Induced Systemic Inflammation Activates Microglia: [(11)C]PBR28 Positron Emission Tomography in Nonhuman Primates - Hannestad, Jonas (2012)
Microglia play an essential role in many brain diseases. Microglia are activated by local tissue damage or inflammation, but systemic inflammation can also activate microglia. An important clinical question is whether the effects of systemic inflammation on microglia mediates the deleterious effects of systemic inflammation in diseases such as Alzheimer's dementia, multiple sclerosis, and stroke. Positron Emission Tomography (PET) imaging with ligands that bind to Translocator Protein (TSPO) can be used to detect activated microglia. The aim of this study was to evaluate whether the effect of systemic inflammation on microglia could be measured with PET imaging in nonhuman primates, using the TSPO ligand [(11)C]PBR28. METHODS: Six female baboons (Papio anubis) were scanned before and at 1 h and/or 4h and/or 22h after intravenous administration of E. coli lipopolysaccharide (LPS; 0.1 mg/kg), which induces systemic inflammation. Regional time-activity data from regions of interest (ROIs) were fitted to the two-tissue compartmental model, using the metabolite-corrected arterial plasma curve as input function. Total volume of distribution (V(T)) of [(11)C]PBR28 was used as a measure of total ligand binding. The primary outcome was change in V(T) from baseline. Serum levels of tumor necrosis factor alpha (TNFα), interleukin-1 beta (IL-1β), interleukin-6 (IL-6), and interleukin-8 (IL-8) were used to assess correlations between systemic inflammation and microglial activation. In one baboon, immunohistochemistry was used to identify cells expressing TSPO. RESULTS: LPS administration increased [(11)C]PBR28 binding (F(3,6)=5.1, p=.043) with a 29±16 % increase at 1h (n = 4) and a 62±34% increase at 4h (n = 3) post-LPS. There was a positive correlation between serum IL-1β and IL-6 levels and the increase in [(11)C]PBR28 binding. TSPO immunoreactivity occurred almost exclusively in microglia and rarely in astrocytes. CONCLUSION: In the nonhuman-primate brain, LPS-induced systemic inflammation produces a robust increase in the level of TSPO that is readily detected with [(11)C]PBR28 PET. The effect of LPS on [(11)C]PBR28 binding is likely mediated by inflammatory cytokines. Activation of microglia may be a mechanism through which systemic inflammatory processes influence the course of diseases such as Alzheimer's, multiple sclerosis, and possibly depression.